TREATMENT OF GENITAL HERPES USING LOCAL THERAPY - Toshev S.U.; Rafikova M.F.; Isaev X.D. (PEDAGOGS, 2024)
Annotation: Genital herpes (GH) is one of the most socially significant problems in the clinical practice of dermatovenerologists, obstetricians, gynecologists, urologists. The number of patients with GH has increased by 30% over the past 10 years. The main role in the etiology of HSV belongs to HSV type 2 (HSV-2), but the pathogens of this pathology can become both HSV type 1 (HSV–1) and a combination of both types of herpes simplex virus. The prevalence of HSV-2 infection in the population ranges from 7 to 40% and averages 20%.